Using Peer Support to Strengthen Mental Health During the COVID-19 Pandemic: A Review - Suresh, Rahul; Alam, Armaghan; Karkossa, Zoe (Frontiers in Psychiatry, 2021)
Background: The coronavirus (COVID-19) pandemic has had a significant impact on society’s overall mental health. Measures such as mandated lockdowns and physical distancing have contributed to higher levels of anxiety, depression, and other metrics indicating worsening mental health. Peer support, which is peer-to-peer provided social and emotional support, is an underutilized and effective mental health resource that can potentially be used to ameliorate mental health during these times. Objective: This review aims to summarize the toll that this pandemic has had on society’s mental health as found in peer-reviewed literature from October 2019 to March 2021, as well as suggest the utility of peer support to address these needs. Methods: References for this review were chosen through searches of PubMed, Web of Science, and Google Scholar for articles published between October 2019 and March 2021 that used the terms: “coronavirus”, “COVID-19”, “mental health”, “anxiety”, “depression”, “isolation”, “mental health resources”, “peer support”, “online mental health resources”, and “healthcare workers”. Articles resulting from these searches and relevant references cited in those articles were reviewed. Articles published in English, French and Italian were included. Results: This pandemic has ubiquitously worsened the mental health of populations across the world. Peer support has been demonstrated to yield positive effects on the mental health of a wide variety of recipients, and it can be provided through numerous accessible mediums. Conclusions: Peer support can be beneficial for improving mental health during the COVID-19 pandemic and may be an effective tool should similar events arise in the future.